Uncoupling between cerebral perfusion and oxygenation during incremental exercise in an athlete with postconcussion syndrome: a case report. Issue 2 (25th January 2017) - Imhoff, Sarah; Malenfant, Simon; Nadreau, Éric; Poirier, Paul; Bailey, Damian M.; Brassard, Patrice
Abstract: High‐intensity exercise may pose a risk to patients with postconcussion syndrome (PCS) when symptomatic during exertion. The case of a paralympic athlete with PCS who experienced a succession of convulsion‐awakening periods and reported a marked increase in postconcussion symptoms after undergoing a graded symptom‐limited aerobic exercise protocol is presented. Potential mechanisms of cerebrovascular function failure are then discussed. Abstract : The case of a paralympic athlete with postconcusion syndrome who experienced a succession of convulsion‐awakening periods and reported a marked increase in postconcussion symptoms after undergoing a graded symptom‐limited aerobic exercise protocol is presented. Potential mechanisms of cerebrovascular function failure are then discussed.